Topology and quantum theory in interaction : NSF-CBMS Regional Conference in the Mathematical Sciences on Topological and Geometric Methods in QFT, July 31-August 4, 2017, Montana State University, Bozeman, Montana - Ayala, David, 1982-; Freed, Daniel S.; Grady, Ryan E., 1985- (Contemporary mathematics (American Mathematical Society), 2018)
This volume contains the proceedings of the NSF-CBMS Regional Conference on Topological and Geometric Methods in QFT, held from July 31-August 4, 2017, at Montana State University in Bozeman, Montana. In recent decades, there has been a movement to axiomatize quantum field theory into a mathematical structure. In a different direction, one can ask to test these axiom systems against physics. Can they be used to rederive known facts about quantum theories or, better yet, be the framework in which to solve open problems? Recently, Freed and Hopkins have provided a solution to a classification pr.